The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1097/bpo.0b013e318202bfcd
|View full text |Cite
|
Sign up to set email alerts
|

Lowest Instrumented Vertebra Selection in AIS

Abstract: Appropriate selection of the lowest instrumented vertebra (LIV) is crucial to ensure positive outcomes after surgical management of patients with adolescent idiopathic scoliosis. Failure to do so can lead to curve decompensation and "adding on" of additional vertebrae to the deformity. Correct identification of the stable, end, and neutral vertebra, whether the curve(s) is structural or nonstructural, and classifying the type of curve are essential aspects of preoperative planning. Evaluating curve flexibility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…1 group, the difference was small and was not noticeable clinically as documented by the results There were some reports [15] concerning the changes in wedging of the adjacent disc or tilt of the last instrumented vertebra. A good correction of ADW and LIVT without loss of correction up to 10 years was achieved in our patients by means of the present method of instrumentation and the determination of the LIV.…”
Section: Discussionmentioning
confidence: 92%
“…1 group, the difference was small and was not noticeable clinically as documented by the results There were some reports [15] concerning the changes in wedging of the adjacent disc or tilt of the last instrumented vertebra. A good correction of ADW and LIVT without loss of correction up to 10 years was achieved in our patients by means of the present method of instrumentation and the determination of the LIV.…”
Section: Discussionmentioning
confidence: 92%
“…2 The studies conducted by Lenke et al 6 suggest the use of bendings in the supine position, the same routine as that adopted by King et al 7 in their classic study on the selection of the arthrodesis site in thoracic scoliosis and other works. 8,9,10 In the authors' clinical practice, it was observed that performing lateralization exams with the patient standing, or with the patient in dorsal decubitus on a table without stabilization of the pelvis, inter-…”
Section: Discussionmentioning
confidence: 99%
“…Although the spontaneous correction of the distal unfused lumbar curve after STF has been widely reported [ 1 , 13 – 20 ]; however, the impact of the spontaneous realignment of unfused segments on disc compensation remains to be quantified. To obtain an optimal balance outcome and prevent radiographical complications, such as the adding-on phenomenon, research has been conducted regarding the optimal LIV selection [ 8 , 21 ], prediction of SLCC [ 14 , 15 , 17 ] and related long-term outcome [ 6 , 22 ]. However, all these studies regarded the unfused distal segments as an ensemble.…”
Section: Introductionmentioning
confidence: 99%